PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - A. Nurul Dzikir; Syahnur Syahnur; Tenriwaru Tenriwaru (Magister Akuntansi, Universitas Atma Jaya Makassar, 2020)
This research aimed to examine whether corporate social responsibility affect the corporate value and whether the profitability as a moderating variable affect the corporate social responsibility and corporate value on mining corporate listed on the Indonesia Stock Exchange (BEI) for the 2016-2018 period. This research used samples from mining companies listed on the Indonesia Stock Exchange (BEI) for the 2016-2018 period as many as 31 issuers and used purposive sampling technique. This research is quantitative descriptive. The data used is secondary data and used data collection methods, namely documentation studies. The data used in this research are financial statement and annual reports by mining companies obtained from the Indonesia Stock Exchange website (https://www.idx.co.id). Based on research results by using the Statistical Product and Service Solution (SPSS 18), shows that CSR affect the corporate value which is proxied to Tobin’s Q, it is known from the calculated t value is greater than the t table value, and the significance value is smaller than the level its significance. And the independent variable CSR and profitability as a moderating are not able to moderate the corporate value, it is known from the value of the relation obtained smaller than the value of CSR to corporate value.